Human resilience depends on distinctively human brain circuitry and development - Reimers, Mark (Frontiers in Behavioral Neuroscience, 2024)
Most studies of psychological resilience in the past century have focused on either biological or social psychological correlates of resilience or depression. This article argues that the two approaches should be integrated because of uniquely human processes of cortical development during early childhood. The article concludes with some suggestions for integrative research agendas.